2017
DOI: 10.3906/biy-1703-104
|View full text |Cite
|
Sign up to set email alerts
|

The MTT viability assay yields strikingly false-positive viabilities although the cells are killed by some plant extracts

Abstract: In the past years, several methods have been developed to determine cell viability in cell culture (Cook and Mitchell, 1989). Among these methods tetrazolium salt-based assays are widely used in order to measure cytotoxicity or cell proliferation (Mosmann, 1983;Berridge et al., 1996).The principle of the MTT [3-(4,5-dimethyl-2thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide] assay is the reduction of water-soluble yellow tetrazolium salt by the dehydrogenase system of metabolically active/live cells into water-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 21 publications
2
47
0
1
Order By: Relevance
“…Bernhard et al [ 62 ] first demonstrated this phenomenon using the CEM-C7H2 lymphocytic leukemia cell line during uptake of resveratrol which chemically reduced MTT molecules inside the cells in the face of declining cell growth. Similar findings have been documented repeatedly with plant extracts to the point where we now consider this MTT phenomenon a signature of such molecules [ 64 ]. Hence, when observed that basolateral SH-SY5Y cells in our co-cultures had declining cell numbers in the face of sustained high MTT metabolism ( Figure 3 ), it most likely means that antioxidant flavonoids from kale juice had traversed the Caco-2Bbe1 barrier and entered these cells.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Bernhard et al [ 62 ] first demonstrated this phenomenon using the CEM-C7H2 lymphocytic leukemia cell line during uptake of resveratrol which chemically reduced MTT molecules inside the cells in the face of declining cell growth. Similar findings have been documented repeatedly with plant extracts to the point where we now consider this MTT phenomenon a signature of such molecules [ 64 ]. Hence, when observed that basolateral SH-SY5Y cells in our co-cultures had declining cell numbers in the face of sustained high MTT metabolism ( Figure 3 ), it most likely means that antioxidant flavonoids from kale juice had traversed the Caco-2Bbe1 barrier and entered these cells.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, to convert MTT to a purple color theoretically would require more mitochondria—which by adding kale juice seems highly unlikely. A subset of the literature shows, however, that purified flavonoids lead to an “artifactual” reduction of MTT dye [ 61 , 62 , 63 , 64 ]. To observe a full comparison of this experiment in the Caco-2Bbe1 cells, please see Supplementary Figure S1 (less dichotomous).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were cultured in Dulbecco's modified Eagle's medium: F12 (DMEM: F12) supplemented with 10% heat-inactivated fetal bovine serum, penicillin (100 U/mL) and streptomycin (100 μg/mL) at 5% CO 2 and 37 C under standard conditions. Cell viability was assessed using MTT assay with slight modifications (16).…”
Section: Percent Inhibition= ( )mentioning
confidence: 99%